TI_GERICHTE 52.2016.257 vom 6. April 2016 , Diniego della licenza edilizia per il risanamento e l'ampliamento di un pontile a lago - TI Tribunale d'appello (2016)
Diniego della licenza edilizia per il risanamento e l'ampliamento di un pontile a lago